Revitalising Effective Community Life Empowerment Through a Real Work Study Programme: (In Payung Village, Weleri District, Kendal Regency) - Ihsan Syifa’ul ‘Afwa; Rafi Al Azhar; Maulida Maghfirotul Mudrikah; Rachmad Fathuriza Adi; Shellya Nur Afifah; Nabilla Aulia Himmawati; Brahmanna Arya Widura; Laila Fitri Nur Zahrani (Universitas Kristen Indonesia Toraja, 2024)
KKN MIT-18 Posko 27 Walisongo State Islamic University Semarang in Payung Village, Weleri District, Kendal Regency is a programme of student service activities to the community. This real work study activity was carried out on 04 July 2024 to 17 August 2024. Service activities carried out in Payung Village include village activities and community activities. This article was created specifically to discuss the activities and roles of students during the implementation of the Community Service Programme. In KKN activities, students involve a lot of the community and village youth. KKN activities also involve elementary, kindergarten, and pre-school children because students also have socialisation programs at schools, as well as opening bimble activities and teaching the Koran. KKN activities are designed to provide practical experience and serve as a learning process for students. The implementation of KKN MIT-18 begins with designing a work programme, conducting a location survey, and socialising with the community. After that, the KKN group adjusted the work programme to the conditions of the village and the needs of the local community. In running the programme, the KKN UIN MIT-18 Walisongo team used various methods, such as counselling, training, and participating in social, cultural, and religious activities in the village. These programmes are tailored to the survey results and community conditions. To ensure that all plans can be carried out well within the 45-day period at the service location, students divide themselves into several groups that have their respective roles. This division aims to optimise the implementation of all planned activities.